Analysis of the Contemporary Scholars on the Alms Donation Practice through E-Commerce - Muh. Ridlal Quddus (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
This research aims to comprehensively analyze the scholars' perspectives regarding the donation practice through e-commerce. The problems proposed include (1) how alms donation practice appears in e-commerce, (2) what is the form of the practice, and (3) what are the perspectives of contemporary scholars on this practice. This research is descriptive qualitative since it uses the library method. Data were collected through juridical, normative (syar'i), and sociological. The results showed that the alms donation practice through e-commerce is legal and there is no argument for prohibiting it. Several scholars recommend people not be familiar with this practice because it contains gharar and syubhat. Moreover, direct alms donation is more advisable since it is a noble deed where people unintentionally obtain the reward of friendship. This research implies that everyone is expected not to doubt the alms donation practice through e-commerce. Additionally, the government is expected to further support this practice.